THE EFFECT OF CFO NARCISSISM, POLITICAL CONNECTIONS, CEO AGE, MANAGERIAL OWNERSHIP AND PROFITABILITY ON AUDIT FEES - Icih Icih; Dewita Febi Silviana (JASS (Journal of Accounting for Sustainable Society), 2023)
Audit fee is the cost incurred by the company for the services of examination of financial statements conducted by external auditors. The amount of audit fees in a company usually tends not to remain every year,this is because there are several factors that are considered in determining the high level of the audit fee. The study aims to test and analyze the influence of CFO narcissism, political connections, CEO age, managerial ownership,and profitability both partially and simultaneously on audit fees. This research is a quantitative study, The population used in this study is a company sector infrastructure, utilities and transportation listed on the Indonesia Stock Exchange for the period 2016 - 2020. The technique of determining the sample uses purposive sampling. The study used multiple linear regression analysis. The results showed that partially CFO Narcissism has a positive effect on audit fees, political connections have a positive effect on audit fees, CEO age has no effect on audit fees, managerial ownership has no effect on audit fees, profitability has a negative effect on audit fees. Audit. As well as CFO narcissism,political connections, CEO age, managerial ownership,and profitability influence simultaneously on audit fees.